Virgil : the Aeneid - Gransden, K. W. (Landmarks of world literature., 2004)
"This guide offers a complete account of the historical setting and significance of The Aeneid, and discusses Virgil's use of Homer's Iliad and Odyssey, as well as the most celebrated episodes in the poem, including the tragedy of Dido and Aeneas' visit to the underworld. The volume examines Virgil's psychological and philosophical insights, and analyzes the poem's status as the central classical work of European culture. The guide to further reading has been updated and will prove an invaluable resource."--Jacket